Simple book keeping assistance for AA Laundry, Yogyakarta - Tri Ratna Purnamarini; Samsi Haryanto (Universitas Muhammadiyah Magelang, 2022)
This community service aims to optimize business financial management by assisting partners in creating and implementing simple bookkeeping. This program is carried out with a gradual mentoring method, start from communication with service partners, assisting in making simple bookkeeping, monitoring progress and producing a simple bookkeeping report. The result of this program provides benefits for AA Laundy's business, so that they are able to make simple bookkeeping properly and correctly. It is hoped that the bookkeeping will be able to help the running of AA Laundry's business.